From Memorization to Morphological Awareness: Developing a Self-Regulated Learning Model for Arabic Vocabulary Acquisition - Ruhul Kudus; Randy; Dyah Adila Perdana; Dessy Sintari Daoed (Al-Muyassar: Journal of Arabic Education, 2026)
The mastery of Arabic vocabulary is currently still dominated by rote memorization patterns which result in surface learning. Students often have difficulty applying vocabulary in new contexts or understanding complex morphological structures. This research aims to develop a Transformative Morphological Self-Regulated Learning (T-MSRL) learning model based on the wazan pattern by integrating morphological awareness, self-regulation, and transformative learning. Using the Research and Development (R&D) method with a 4D (Define, Design, Develop, Disseminate) model, the research was conducted on Arabic Language Education students at Universitas Negeri Makassar. The research instruments included vocabulary mastery tests, independent questionnaires, and observation sheets. The results of the study show that the T-MSRL model is very valid according to expert judgment and practical to apply. The effectiveness test proved that students who used this model experienced significant improvements in vocabulary mastery, morphological awareness, and self-regulation skills compared to the control class. The T-MSRL model has succeeded in changing the paradigm of student learning from mere memorization to in-depth and systematic morphological analysis.